The Influence Of Social Support And Digital Literacy Ability On Students’ Self-Efficacy - Solahudin, Makmur; Sujiarto, Heru; Mudrikah, Achmad; Kosasih, Usep (CV. Inara, 2022)
The digital era brings students to various conveniences as well as challenges in the learning process. The learning mindset is no longer about the process of direct interaction between students and lecturers. Instead it has shifted to a single process of finding things out from all sources. Digital literacy ability, belief and self-confidence of students are needed in completing lecture assignments properly and on time. This study aims to analyze the effect of social support, digital literacy ability on student self-efficacy in the Depok City area. This study uses a quantitative approach with a survey method. The population is all students studying in Depok City with a sample of 410 students taken by random sampling. The results showed that the direct effect of social support on self-efficacy was indicated by the path coefficient value of 0.200 sig value. 0.000, the direct effect of digital literacy ability on self-efficacy is indicated by the path coefficient value of 0.344, the value of sig. 0.000, the simultaneous effect of social support, digital literacy abilityon self-efficacy is indicated by the coefficient value of 0.210, Sig. F change. 0.000. From the results of the study, it can be concluded that social support and digital literacy ability have a positive and significant effect on self-efficacy individually or simultaneously.